Catalytic removal of nitrates from waters - Constantinou, Costas L.; Efstathiou, Angelos M.; Costa, Costas (My University, 2010)
The selective catalytic reduction of nitrates (NO3) in pure water towards N2 formation by the use of gaseous H2 and in the presence of O2 (air) at 1 atm total pressure and 25◦C has been investigated over PdCu supported on TiO2-Al2O3 pellets (spherical shape). The effects of internal mass transport phenomena, of Pd and Cu loading (wt%), and of reducing feed gas composition on the reaction rate, N2-selectivity, and the kinetics of the overall reaction in terms of apparent reaction orders with respect to nitrate concentration (mg/L) and H2 partial pressure (bar) have been investigated. Apparent reaction orders of 0.32 and 1.04 were estimated, respectively with respect to NO3 − concentration and H2 partial pressure in the reducing feed gas stream (H2/He). However, when 20% air is added in the hydrogen reducing feed gas stream, the apparent reaction order with respect to the H2 partial pressure was increased to 1.7. It is demonstrated for the ﬁrst time that the presence of internal mass transport phenomena when large catalytic particles (2–3 mm in size) are used in a semi-batch mode reactor operation results in the reduction of the selectivity of reaction with respect to NH4 + and NO2 − products, and at the same time in the increase of N2 product selectivity, whereas the opposite is true for the rate of reaction. Moreover, it was found that the reaction rate, the NO3 − conversion (%), and the reaction product selectivity are affected signiﬁcantly by the presence of oxygen in the reducing feed gas stream, and by the Pd and Cumetal loading used in catalyst’s composition.
Keywords: Mass transfer; Nitrates